ANALISA FAKTOR YANG PENTING DARI DIMENSI ELECTRONIC WORD OF MOUTH (EWOM) BAGI KONSUMEN DALAM MEMILIH HOTEL DI SITUS ONLINE TRAVEL AGENT (OTA) - Vania Karunia Utami; Daniel Tanujaya; Regina Jokom (Institute of Research and Community Outreach - Petra Christian University, 2015)
Online Travel Agent (OTA) is an e-commerce which facilitates its customers to buy various tourism products (e.g. hotel rooms). During hotel selection process on OTA, customers tend to look for information such as Electronic Word of Mouth (eWOM) or review. eWOM has 13 dimensions that were analyzed based on its importance. This research is conducted to find out which factors are important for customers when selecting a hotel on OTA. The research type is quantitative descriptive using exploratory factor analysis. The analysis showed that there are 3 important factors: content of review, source credibility, writing style and recommendation rating. Content of review is the most important factors among those 3 factors according to its contribution in hotel selection.